"You only live twice": multidisciplinary management of catastrophic case in placenta Accreta Spectrum-a case report - David Atallah; Hicham Abou Zeid; Malak Moubarak; Maya Moussa; Nadine Nassif; Victor Jebara (BMC, 2020)
Abstract Background Placenta percreta is associated with high hemorrhagic risk and can be complicated with fatal thromboembolic events. Involving a multidisciplinary team in the treatment of these patients is mandatory to reduce morbidity and mortality. Case presentation This paper reports the case of a 22-year-old patient with placenta percreta who was referred to our tertiary care center for delivery. Few hours after undergoing a successful cesarean hysterectomy, the patient developed a pulmonary embolism and cardiac arrest. A transthoracic echocardiogram done in the intensive care unit (ICU) showed a thrombus in the right ventricle. After cardiac resuscitation, the patient underwent an urgent thoracotomy and a pulmonary artery thrombectomy; many clots were retrieved from the pulmonary artery. After weaning from extracorporeal circulation, an intraoperative transesophageal cardiac ultrasound enabled the medical team to detect a new free-floating thrombus in the right atrium and right ventricle, and consequently to perform an embolectomy and prevent the patient's death. Conclusion This case emphasizes the role of multidisciplinary team in treating high-risk obstetric cases that could be complicated with massive and fatal thromboembolic events. The use of intraoperative transthoracic echocardiography helps in detecting a new thrombus and guides the anesthesiologist in the intra-operative monitoring.